Recent advancements in garbled computing: How far have we come towards achieving secure, efficient and reusable garbled circuits. (15th April 2018) - Saleem, Ahsan; Khan, Abid; Shahid, Furqan; Masoom Alam, M.; Khan, Muhammad Khurram
Abstract: Secure function evaluation (SFE) is a cryptographic protocol that facilitates participants to compute a function on their private inputs in such a way that privacy of their inputs is preserved. In early 80's Andrew Yao proposed a solution for secure function evaluation known as garbled circuits based on series of Boolean gates and encryption of truth tables. The approach was thought to be theoretically very appealing, however, the scheme was not practical due to sever implementation issues in its efficiency and reusability. However, since then the garbled circuits have evolved and the common notion of impractical garbled circuit have changed greatly mainly due to great deal of interest shown and efforts made by the researchers in a bid to make Yao's garbled circuits practical. In this paper we have analyzed some of the most significant contributions of researchers in enhancing various aspects of garbled circuits and provided a comprehensive comparative analysis and discussed the pros and cons of such schemes. Furthermore, we provide a classification of existing garbled circuit schemes in the form of a comprehensive thematic survey. We conclude our paper by providing new research directions in this domain for new researchers.